New Media and Research Dissemination: The Case of Performing Mathematics Education Research - Gadanidis, George; Borba, Marcelo [UNESP] (My University, 2013)
Academic research is typically written in a style and for ven-ues that remain largely inaccessible by the general public and even by the practitioners who might benefit from it. In this article we discuss a research dissemination project that takes on the challenge of using new media and alternative forms of research communication: research-based songs, art, and mini-documentaries to be shared publicly through You-tube, live performances, and broadcast media, with the target audience being K-8 students, teachers, parents, educational organizations and the public. We purposely create a parallel between our classroom-based research focus on mathematics performance and the dissemination of our findings through new media research performance, by relying on performance ethnography methods.